Comparison of Zinc Supplementation versus Placebo in Addition to Standard Therapy for Management of Children with Pneumonia - Kazi, Tahreem; Hussain, Syed Asif; Hussain, Zahid; Shehzad, Muhammad Asad; Gulfam, Shehzadi; Khan, Sajeela (Journal of Postgraduate Medical Institute, 2024)
Objective: To compare the mean hospital stay with zinc supplementation vs placebo in standard therapy for management of pneumonia in children. In children with pneumonia, zinc supplements have been shown to enhance the remission of clinical symptoms. Study Design: Randomized controlled trial Duration and place of study: Pediatric department Nishtar Hospital, Multan This study was conducted from Jan 2019 to Feb 2020. Methodology: Two hundred and forty children were enrolled and divided into two groups. In group I, children were given 20mg per 5ml solution of zinc supplementation with standard therapy for pneumonia, while in group II, children were given 20 mg of placebo along with standard therapy for pneumonia. The patients were discharged, and the resolution of symptoms and total stay in the hospital were noted. Data was collected, and statistical analysis was performed using SPSS-20. Results: The mean age of patients was 4.42±2.71years, and there were 85 (70.8%) males and 35 (29.2%) females in group 1, while the mean age of patients was 4.71±3.04 years, and there were 82 (68.3%) males and 38 (31.7%) females in group II. The mean duration of hospital stay in the zinc group was 100.14±16.83 hours, and in the placebo group was 123.34±15.38hours. The difference was highly significant (p <0.05). Conclusion: Thus, zinc supplementation is beneficial in the early resolution of symptoms of pneumonia, and there is a reduction in the hospital stay of children.